Distribution Land Surface Temperature (LST) Using Spatial Method Based on Landsat 8 Images in Manggarai, Nusa Tenggara Timur in Periode of June-July 2015-2019 - Yatimas Murni, Lorensia; Yuliara, I Made; Windaryoto, Windaryoto (BULETIN FISIKA, 2021)
Population growth and rapid development have resulted in reduced availability of vacant/open vegetated land, thus affecting changes in land surface temperature (LST). Land surface temperature is the temperature on the earth's surface which is the result of the reflection of objects recorded by satellite images at a certain time. In this study, LST processing was carried out in Manggarai Regency, NTT for the period June July 2015-2019, using a spatial method based on Landsat 8 images. From the processing results, the LST distribution, minimum and maximum temperatures were obtained. The highest LST distribution in Manggarai Regency, NTT does not only occur in the downtown area, namely Langke Rembong District, but also occurs in suburban areas, namely the Northeast of Reok District and Wae Ri'i District. The highest LST in Manggarai Regency, NTT was on the image on July 7 2018 which reached 42,312  o C while the lowest LST was on the image on July 4, 2017 of -59,307 o C. When viewed from the average LST obtained, the highest average LST is in the image on July 7 2018 with an average LST of 25.683  o C while the LST with the lowest average is in the image on July 4, 2017 with an average LST of 5,218 o C.